Tensor Categories and Hopf Algebras - Andruskiewitsch, Nicolás (Contemporary Mathematics Ser., 2019)
This volume contains the proceedings of the scientific session ""Hopf Algebras and Tensor Categories"", held from July 27-28, 2017, at the Mathematical Congress of the Americas in Montreal, Canada. Papers highlight the latest advances and research directions in the theory of tensor categories and Hopf algebras. Primary topics include classification and structure theory of tensor categories and Hopf algebras, Gelfand-Kirillov dimension theory for Nichols algebras, module categories and weak Hopf algebras, Hopf Galois extensions, graded simple algebras, and bialgebra coverings.